Unusual Metachronous Renal Pelvis and Colon Metastases in a Patient with Endometrial Cancer: A Case Report - Juin Kim; Chul-min Lee; Bo-Kyeong Kang; Mimi Kim (Journal of the Korean Society of Radiology)
Endometrial cancer commonly metastasizes to the pelvic and para-aortic lymph nodes, vagina, peritoneum, and lungs. Unusual sites of metastasis include the bone, brain, abdominal wall, muscles, and intra-abdominal organs. To our knowledge, there have been no documented cases of synchronous or metachronous metastasis of endometrial cancer to the renal pelvis or colon. Metastatic tumors in the renal pelvis and colon indicate nonspecific radiological findings, making them difficult to distinguish from primary tumors. We describe a case of a 55-year-old female previously treated for endometrial cancer, who was subsequently found to have metastatic masses in the renal pelvis and colon. The two masses were initially misidentified as primary urothelial carcinoma and colon adenocarcinoma.